In vitro studies and stigmasterol production from Wedelia biflora (L.) D.C / Siti Norayu Idris - Siti Norayu, Idris (2017)
Wedelia biflora Linn. D.C belongs to the family Asteraeceae and one of the potential medicinal plants. In the present study, callus induction procedure from stem and leaf explants of W. biflora was established via manipulation of auxins and cytokinins; and further improved by manipulation of abiotic stress conditions (sucrose concentration, incubation temperature, light colours and photoperiod). Combination of 2.0 mg/L NAA and 3.0 mg/L BAP promoted the best callus formation from stem explants (98% callus formation); whereas 1.0 mg/L 2,4-D and 3.0 mg/L BAP was the best combination for leaf explants (96% callus formation). The formation of callus was further improved by application of 4% of sucrose concentration, 25°C incubation temperature and incubated in total darkness for stem callus; and application of 3% sucrose, incubation at 30°C under white light and exposed to 8 h light/16 h darkness improved the growth of leaf callus. Further subculture of selected healthy callus onto 3.0 mg/L BAP and 2.0 mg/L IBA media resulted in complete regeneration of plantlets. Internodal explants of W. biflora successfully regenerated whole plantlets by application of 1.0 mg/L BAP and 1.0 mg/L IBA in half-strength MS medium. Consequently, indirect organogenesis was established by using the previously obtained healthy callus and direct organogenesis accomplished by using internodal segments of W. biflora. The methanolic extracts from the callus were compared with in vivo and in vitro grown explants extracts in terms of antimicrobial and antioxidant activities; and the stigmasterol content was screened in all those extracts by using spectrophotometer method and clarified by HPLC analysis. Stem callus treated with 4% sucrose and in vivo leaf as well as in vivo stem extracts gave potent antimicrobial activity, especially towards Bacillus subtilis (13 mm, 12 mm and 11 mm, respectively) and Candida albicans (16 mm, 14 mm and 13 mm, respectively). Those three extracts also showed higher antioxidant ability when assayed with DPPH radical scavenging assay (IC50: 250, 251 and 297 mg/L, respectively), H2O2 radical scavenging assay (IC50: 272, 299, and 301 mg/L, respectively), reducing power activity assay (absorbance at 700 nm: 2.21, 2.00 and 1.96, respectively) and ferric reducing antioxidant power assay (antioxidant power: 720.82, 639.00 and 520.82 mM Fe (II)/g dry weight, respectively). Estimation of stigmasterol in stem callus grown with 4% sucrose, in vivo stem and in vivo leaf showed higher stigmasterol content; 0.088, 0.078 and 0.066 mg/g, respectively. Results from this research enable callus derived from stem explants and improved with 4% sucrose concentration to be used in mass production of bioactive compound (stigmasterol) which is responsible for the antimicrobial and antioxidant activities in this plant. This study is the first report in callus induction and regeneration of W. biflora with in vitro stigmasterol production.